Tafsir Tematik Konsep Kemiskinan Dalam Al-Qur’an: Pendekatan Semantik Dan Kontekstual Bahasa Arab - Lenni Suriyanti; Sohra; Rosmini Amin; Amiruddin (CV. SINAR HOWUHOWU, 2026)
issue, but also as a social, moral, and structural reality. Understanding the concept of poverty in the Qur'an requires a comprehensive approach, especially through the analysis of Arabic as the primary medium of revelation. This article aims to examine the concept of poverty in the Qur'an using the thematic interpretation method (al-tafsīr al-mawḍū‘ī) through a semantic and contextual approach to Arabic. This research is a qualitative study with primary data sources in the form of Qur'anic verses related to poverty, as well as secondary data sources in the form of classical and contemporary commentaries, Arabic dictionaries, and linguistic literature. The analysis was carried out by inventorying related verses, then examining the lexical and contextual meaning of poverty vocabulary such as faqīr, miskīn, and other related terms through the study of dalālah and siyāq al-lughawī, and considering the socio-historical context of the revelation of the verses. The study's findings demonstrate that the concept of poverty in the Qur'an has a multi-layered and dynamic meaning, encompassing economic, social, and ethical dimensions, and emphasizing individual and collective responsibility in realizing social justice. A semantic and contextual approach to Arabic enriches the understanding of thematic interpretation by presenting a more accurate, proportionate, and relevant interpretation to the context of contemporary life.